Improving Financial Statement Translation Methodology under IAS 21 for Cross-Border Business in Globalized Economies - Abrorbek Kozimjonov (Apollo: Journal of Tourism and Business, 2026)
The intensification of globalization and economic integration, the expansion of transnational corporations, and the growing inflow of foreign investment have made the preparation of financial statements in accordance with International Financial Reporting Standards (IFRS) increasingly necessary. Today, financial reporting is regarded not merely as a source reflecting an entity's financial position and performance, but as an integrated information system used by investors, creditors, government authorities, and other stakeholders for economic decision-making. In this context, it is essential to scientifically substantiate the procedures for translating accounting information prepared in a functional currency into a presentation currency. Ensuring the reliability, consistency, and international comparability of financial reporting indicators, while preserving the interrelationship between income and expenses, assets and liabilities, equity items, net profit, and other comprehensive income, is one of the priority research directions for improving financial reporting methodology. Using the case of a Tashkent-based joint-stock company, this article examines the problems of translating financial statements from a functional currency into a presentation currency and proposes a weighted-average-rate methodology as a solution.